An ultra-wideband plasmonic reflector based on local resonant bandgap and Bragg bandgap - Chen, San; Fang, Liang; Liu, Jianqiang; Wu, Shan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
Unlike previous reports that utilized periodic modulation of insulation layer thickness or dielectrics, we propose the use of split ring resonators (SRRs) and their arrays to modulate the propagation characteristics of MIM plasmon waveguides. Due to the strong resonance backscattering of SRR, resonance transmission valleys appear in the transmission spectra of MIM waveguides. Changing the size of SRR can achieve continuously adjustable positions of resonance transmission valleys. The introduction of SRRs periodic arrays will result in two bands (bandgaps) with transmission minimum in the transmission spectra. Combining the dependence of the two bandgaps on the array period and the field distribution, the two bandgaps are Bragg bandgaps and local resonance bandgaps, respectively. By modulating the local resonance bandgap, the Bragg bandgap can be tuned. The introduction of local bandgap increases the degree of freedom to modulate the transmission characteristics of MIM waveguides. Combining local resonant bandgap and Bragg bandgap can significantly increase the reflection bandwidth, achieve broadband filtering, and facilitate the miniaturization of waveguide devices.
Optica Applicata, Vol. 54, 2024, nr 2, s. 205-216
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; metal-insulator-metal waveguides; SRRs; Bragg bandgap; local resonant bandgap